Towards a methodological guide to share knowledge when creating open educational resources - Espinoza-Guzmán, Julia; González, Liliana; Forero, Sergio; González, Ana María (LACLO 2016, 2016)
People claim the right to study and learn what they desire, when and where they want; for this reason it is necessary to offer flexible training methods that provide real opportunities for independent learning. In order to help solve this need, this article presents a methodological guide (MG) so people without experience or knowledge in software development can create, autonomously, Open Educational Resources (OER) executable in mobile equipment. In addition to MG, is presented a systematization process of experience and the implementation through a case study carried out in Mexico and Costa Rica. As a result participants created REA and appreciated the autonomy provided by the MG on average with 8 of 10 points.
© © 2016 IEEE. Personal use of this material is permitted. Permission from IEEE must be obtained for all other uses, in any current or future media, including reprinting/republishing this material for advertising or promotional purposes, creating new collective works, for resale or redistribution to servers or lists, or reuse of any copyrighted component of this work in other works
Keywords: Guía Metodológica; App Inventor; Recursos Educativos Abiertos; Autonomía; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education::Subject didactics